2022
DOI: 10.5194/soil-8-59-2022
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between compost and cover crops in a Mediterranean row crop system leads to increased subsoil carbon storage

Abstract: Abstract. Subsoil carbon (C) stocks are a prime target for efforts to increase soil C storage for climate change mitigation. However, subsoil C dynamics are not well understood, especially in soils under long-term intensive agricultural management. We compared subsoil C storage and soil organic matter (SOM) composition in tomato–corn rotations after 25 years of differing C and nutrient management in the California Central Valley: CONV (mineral fertilizer), CONV+WCC (mineral fertilizer and cover crops), and ORG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 144 publications
(152 reference statements)
1
5
0
Order By: Relevance
“…This subsurface effect of CC may be masked by frequent disturbance in the ST treatments. This observation is consistent with recent studies that have shown that the effect of cover crops extends below the so-called "plough layer" (rooting depth of approximately 30 cm) (Rath et al, 2022;Veloso et al, 2018;Sastre et al, 2018;Tautges et al, 2019).…”
Section: Water Retentionsupporting
confidence: 93%
“…This subsurface effect of CC may be masked by frequent disturbance in the ST treatments. This observation is consistent with recent studies that have shown that the effect of cover crops extends below the so-called "plough layer" (rooting depth of approximately 30 cm) (Rath et al, 2022;Veloso et al, 2018;Sastre et al, 2018;Tautges et al, 2019).…”
Section: Water Retentionsupporting
confidence: 93%
“…Rath et al. (2022) in an SDI maize‐tomato rotation in California found the greatest mineral N during the growing season in June and the least mineral N in winter months (i.e., November to February). Similar to the temporal trend reported in the current study, Geisseler et al.…”
Section: Resultsmentioning
confidence: 99%
“…We sampled only a handful of sites and treatments and, within each site, a single time point. Additionally, our analysis focused solely on topsoils (0–15 cm), though it is well-known that management practices, such as tillage and OM amendments, can also alter subsoil C dynamics. Rather than measuring long-term biomass inputs, we assumed that within a single site, cultivated soils had similar biomass inputs and uncultivated soils would have greater biomass inputs than the cultivated soils. We did not directly quantify mineral and/or particulate organic C, and we investigated only a handful of soil C processes, neglecting to examine microbial vs plant-derived C or carbon use efficiency – though the utility of these measures is sometimes questioned. , In order to gain a more wholistic understanding of anoxic microsites and soil C response to management, weather events, climate change, and various soil properties, additional studies examining a broader range of sites, soil depths, management practices, and soil processes will be required.…”
Section: Resultsmentioning
confidence: 99%